|
|
|
|
|
Note:
|
π0T × Ҏ[ success in T0 ] + π1T × Ҏ[ success in T1 ] + π2T × Ҏ[ success in T2 ] S = --------------------------------------------------------------------------------- π0T0 + π1T1 + π2T2 π0T × 0 + π1T × Ҏ[ 0 arrival in τ sec ] + π2T × 0 <=> S = ---------------------------------------------------------- π0T0 + π1T1 + π2T2 π1T × e-gτ <=> S = --------------------- .......... (1) π0T0 + π1T1 + π2T2 |
Notes:
|
|
Hence:
|
|
1 T0 = --- ........ (2) (See: click here) g |
|
|
|
(For detail on why you have &tau in the expression, see: click here)
Therefore:
E[T1] = T + τ + E[y] |
For a Poisson arrival process with arrival rate g, we have previously determined that (see: click here)
1 - e-gτ y = τ - --------- ........ (3) g |
E[T1] = T + τ + E[y] |
|
|
|
E[T2] = E[T1] |
OK, we got expressions for
T0,
T1 and
T2....
Now we find the steady state probabilities
π0,
π1 and
π2....
(We get to finally use this !!! :-))
|
Consider the state transition diagram:
π0 = π0p00 + π1p10 + π2p20 π1 = π0p01 + π1p11 + π2p21 π2 = π0p02 + π1p12 + π2p22 |
|
Result after substitution:
Before substitution: π0 = π1p10 + π2p20 π1 = π0 + π1p11 + π2p21 π2 = π1p12 + π2p22 |
Result:
π0 = π1p10 + π2p10 |
> eq1 := q0 = p10*q1 + p10*q2; eq1 := q0 = p10 q1 + p10 q2 > eq2 := q2 = p12*q1 + p12*q2; eq2 := q2 = p12 q1 + p12 q2 > eq3 := q0 + q1 + q2 = 1; eq3 := q0 + q1 + q2 = 1 > solve( { eq1, eq2, eq3 }, {q0, q1, q2} ); p12 -1 + p12 p10 {q2 = -------, q1 = - --------, q0 = -------} 1 + p10 1 + p10 1 + p10 |
p10 + p11 + p12 = 1 (this is the sum of all "exit" probabilities from state 1) |
Therefore, we can rewrite the solution as:
p10 π0 = --------- ........ (6) 1 + p10 p10 + p11 π1 = ----------- ........ (7) 1 + p10 1 - p10 - p11 π2 = -------------- ........ (8) 1 + p10 |
Note:
|
Observation 1:
|
Observation 2:
|
p10 = Ҏ[ 0 arrivals in (T + y) sec ] |
If y were a constant, the solution would be simple:
(g(T + y))0 ---------- e-g(T + y) (Poisson arrivals) 0! |
BUT, y is a random variable
(We divide the range "[0, τ]" into individual time instances u)
p10 = ∑τu=0 Ҏ[ 0 arrivals in T + y | y = u ] × Ҏ[ y = u ] (Law of Tatal Probability) = ∑τu=0 Ҏ[ 0 arrivals in T + u ] × Ҏ[ y = u ]
|
We now only have to compute p11 before we can find the throughput formula for the 1-persistent CSMA protocol....
Note:
|
Observation 1:
|
Observation 2:
|
p11 = Ҏ[ 1 arrival in (T + y) sec ] |
Again, if y were a constant, the solution would be simple:
(g(T + y))1 ---------- e-g(T + y) (Poisson arrivals) 1! |
BUT, y is a random variable
(We divide the range "[0, τ]" into individual time instances u)
p11 = ∑τu=0 Ҏ[ 1 arrival in T + y | y = u ] × Ҏ[ y = u ] (Law of Tatal Probability) = ∑τu=0 Ҏ[ 1 arrival in T + u ] × Ҏ[ y = u ]
|
gT e-g(T+2τ) [ 1 + gT + gτ(1 + gT + gτ/2) ] S = -------------------------------------------- ........ (11) g(T + 2τ) - (1 - e-gτ) + (1 + gτ)e-g(T+τ) |
Substitutions used to normalize the throughput expression:
g = offered packet rate per sec G = gT ....... (11) = offered packet rate per packet transmission time T |
gT e-g(T+2τ) [ 1 + gT + gτ(1 + gT + gτ/2) ] S = -------------------------------------------- ........ (11) g(T + 2τ) - (1 - e-gτ) + (1 + gτ)e-g(T+τ) gT e-(gT+2gτ) [ 1 + gT + gτ(1 + gT + gτ/2) ] = -------------------------------------------- (Subst: G = gT) (gT + 2gτ) - (1 - e-gτ) + (1 + gτ)e-(gT+gτ) G e-(G+2gτ) [ 1 + G + gτ(1 + G + gτ/2) ] = ------------------------------------------ (Subst: aG = gτ) (G + 2gτ) - (1 - e-gτ) + (1 + gτ)e-(G+gτ) G e-(G+2aG) [ 1 + G + aG(1 + G + aG/2) ] = ------------------------------------------ (Rewrite nicer...) (G + 2aG) - (1 - e-aG) + (1 + aG)e-(G+aG) G e-G(1+2a) [ 1 + G + aG(1 + G + aG/2) ] = ------------------------------------------ ......... (12) G(1 + 2a) - (1 - e-aG) + (1 + aG)e-G(1+a) |
This is the classic form for the throughput of 1-persistent CSMA
1-persistent CSMA performs slightly better at lighter loads